Managing Mixed Language Proficiency in English Classes: Challenges and Strategies for Vocational Students - Lubis, Darliyati; Daulay, Sholihatul Hamidah (Yayasan Insan Cipta Medan, 2026)
This study aims to examine how English language teachers address diverse language proficiency levels in vocational high school (SMK) classrooms in Indonesia, where students exhibit varying linguistic abilities and learning motivations. Using a qualitative descriptive approach, data were collected from six English language teachers through semi-structured interviews, classroom observations, and document analysis. The data were analysed using thematic analysis to identify common challenges, strategies employed and their impact on instruction. The results indicate that teachers face significant challenges in adjusting lesson pace, student participation and fair assessment due to wide proficiency differences and limited school support. Despite this, they employ differentiation strategies such as graduated tasks, flexible grouping, graduated support, and limited use of the mother tongue to ensure inclusive learning. These adaptive practices align with Vygotskys Sociocultural Theory and Tomlinsons Differentiated Instruction Framework. The study concludes that managing proficiency diversity requires context-specific teaching approaches, institutional support, and professional development for teachers to transform classroom diversity into a valuable learning resource.